The Effect of a Self-Care Practice-Based Supportive Educative System on Knowledge, Self-Efficacy, and Medication Compliance in Pulmonary Tuberculosis Patients in Blitar Regency, Indonesia - As'ad Faishal; Indasah; Joko Prasetyo (Journal Public Health and Clinical Science, 2026)
Prevention of Pulmonary Tuberculosis in Indonesia has become an important agenda because the number of sufferers is increasing. Regencies in Indonesia, including Blitar Regency, are highly endemic for Pulmonary Tuberculosis, so mitigation is necessary for sufferers. This disease can be cured, provided that sufferers have knowledge about their disease, have the motivation to recover and comply with health recommendations, namely regularly taking medication. This study was conducted in Blitar Regency, East Java Province, Indonesia with a sample of 85 patients with Pulmonary Tuberculosis. Patients were divided into two groups, where the first group was given minimal treatment according to government regulations, while the second group was given additional treatment.Supportive Educative System Based Self Care Practice. The result is that Supportive Educative System Based Self Care Practicecan provide patients with knowledge about the disease they are suffering from, thus motivating them to recover and raising awareness among these patients to comply with taking medication, so that patients can be cured.